Persepsi Peserta Program Pertukaran Mahasiswa Merdeka tentang Citra Kampus yang Multikultural : Studi Deskriptif Kualitatif di Universitas Muhammadiyah Malang - Nailah Azizah Firdausi; Tria Patrianti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Multicultural campuses are growing in awareness of the importance of diversity in the higher education experience. Through the independent student exchange program, unity in diversity is strengthened. It is important for Universitas Muhammadiyah Malang to maintain its image as a multicultural campus. This study aims to examine the perceptions of independent student exchange program participants about the image of a multicultural campus. This research uses the theory of Image and Perception. Data analysis was carried out with descriptive qualitative. The results of this study, First, Selection, the Independent Student Exchange Program is considered very good by participants because it provides many benefits. They gained valuable memories, such as meeting new friends, learning new cultures, and gaining valuable practicum experience. Second, Organization, the Merdeka Student Exchange Program at Universitas Muhammadiyah Malang provides students with the opportunity to learn outside the classroom with education from destination universities. Participants experience differences in character and accent from other students, highlighting the importance of communicating well in a multicultural campus environment. Third, Interpretation, the Merdeka Student Exchange Program reflects students' drive for self-development and exploration of potential and encourages understanding of the diversity of ethnicity, nation, culture, race, and religion.